PENGARUH MOTIVASI KERJA TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI DAN KEDISIPLINAN SEBAGAI VARIABEL MEDIATOR PADA SMP NEGERI KOTA LHOKSEUMAWE - Dewi Rahmani; Apridar Apridar; Naufal Bachri (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study aims to examine the effect of work motivation on teacher performance with organizational commitment and discipline as a mediator variable in the junior high school in Lhokseumawe City. The data used in this study are primary data of 150 respondents. Data analysis method in this research uses structural equation model with the help of analysis of moment structure. The results showed that work motivation and organizational commitment affect teacher performance, work motivation affects organizational commitment and motivation affects work discipline. While work discipline has no effect on teacher performance. But organizational commitment is able to mediate the relationship between work motivation on teacher performance. But work discipline is unable to mediate the relationship between work motivation and the performance of Lhokseumawe City Middle School teachers.